Profile of Syphilis Compliance and Success of Therapy at Dermatology and Venereology Clinic RSUD Dr. Saiful Anwar Malang: A Descriptive Study - Donoseputro, Intan Wasaputri; Setyowatie, Lita (Universitas Airlangga, 2024)
Syphilis is a chronic progressive sexually transmitted infection, that causes a life-threatening condition if left untreated. In lower-middle-income countries, the burden of disease might appear to be lower due to a lack of reports. This study aimed to report the epidemiological profile, the profile of compliance, and the success of therapy of syphilis at the Dermatology and Venereology Outpatient Clinic in RSUD dr. Saiful Anwar Malang, Indonesia. This study used a descriptive approach using secondary data from the medical records of newly diagnosed syphilis patients at Dermatology and Venereology Clinic RSUD dr. Saiful Anwar Malang from January 2021 - December 2021. Sample collection was using a total sampling technique. Eighteen medical records met the inclusion criteria. The majority of samples were men (77.8%), aged 17-25 years (44.4%) and 26-35 years (44.4%), had a high school education (55.6%), HIV positive (50%) and HIV negative (50%). All 18 patients got intramuscular injections of a single 2.4 million U or 7.2 million U Benzathine Penicillin G according to the syphilis stage. It was found that eight patients (44.4%) had a successful therapy, two patients (11.2%), experienced failure, and the remaining eight patients (44.4%) were unknown due to loss of follow-up. Several factors are associated with better patient compliance including older age, higher educational level, type of the disease, and lower complexity of treatment schedules. Overall, therapeutic compliance of syphilis patients is good, but monitoring compliance needs to be improved. Benzathine Penicillin G remains the drug of choice for syphilis and has a high success rate.